2022
DOI: 10.3390/gels8100608
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication and Characterizations of Pharmaceutical Emulgel Co-Loaded with Naproxen-Eugenol for Improved Analgesic and Anti-Inflammatory Effects

Abstract: The aim of this study was to fabricate and characterize a pharmaceutical emulgel co-loaded with naproxen/eugenol for transdermal delivery to improve the analgesic and anti-inflammatory effects and to eliminate GIT adverse reactions. Emulgel was prepared using a slow emulsification method and evaluated for physical appearance, thermodynamic stability, viscosity, pH, spreadability, extrudability, in-vitro drug release, drug content, ex-vivo permeation, drug retention studies and in-vivo studies. The emulgel exhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 33 publications
0
13
0
2
Order By: Relevance
“…The M-βCD:CA MIP-NSs 1:8 (10% Melatonin) cream formulation had the highest apparent viscosity. The viscosity is an important property for the processing, handling of the products, and controlling of the drug release since it can affect the therapeutic efficiency of the formulation [ 105 ]. The viscosity was higher for M-βCD:CA MIP-NSs 1:8 cream formulation rather than the βCD:CA MIP-NSs 1:8 cream formulation [ 25 , 26 ], an observation that can be related to the swelling capacity and spreadability of MIP-NSs and NIP-NSs (as displayed in Table 3 and Table S1 in Supplementary Materials ).…”
Section: Resultsmentioning
confidence: 99%
“…The M-βCD:CA MIP-NSs 1:8 (10% Melatonin) cream formulation had the highest apparent viscosity. The viscosity is an important property for the processing, handling of the products, and controlling of the drug release since it can affect the therapeutic efficiency of the formulation [ 105 ]. The viscosity was higher for M-βCD:CA MIP-NSs 1:8 cream formulation rather than the βCD:CA MIP-NSs 1:8 cream formulation [ 25 , 26 ], an observation that can be related to the swelling capacity and spreadability of MIP-NSs and NIP-NSs (as displayed in Table 3 and Table S1 in Supplementary Materials ).…”
Section: Resultsmentioning
confidence: 99%
“…PEG was used in nimesulide emulgel which act as a permeation enhancer. After application, integrity of stratum corneum got changed, leading to enhanced percutaneous absorption of developed formulation as compared to marketed product [ 44 ]. Statistically, the outcomes of the study, analgesic effect, were found significantly different ( p < 0.05) for the treated group as compared to control group in the student’s t -test.…”
Section: Resultsmentioning
confidence: 99%
“…PEG was used in nimesulide emulgel which act as a permeation enhancer. After application, integrity of stratum corneum got changed, leading to enhanced percutaneous absorption of developed formulation as compared to marketed product [43]. Statistically, the outcomes of the study, analgesic effect, were found signi cantly different (p < 0.05) for the treated group as compared to control group in the student's t-test.…”
Section: In-vivo Analgesicmentioning
confidence: 95%